Evaluation of Economic Values of the 1st Plain of Jars Tourist Attraction in Xiengkhouang Province - XIONGTOUA, Tongvang; CHANTHAVONE, Thongphanh; KINGSADA, Youtthasack; THAMMAVONG , Vanhxay; SOULISACK, Sithat (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This paper evaluates the economic values of the 1st Plain of Jars Tourist Attraction in Xiengkhouang Province. It found out that 318 domestic visitors and 82 foreign visitors are willing to pay for the renovation and maintenance of the plain of jar. In terms of local visitors, the most willing to pay for the fee is 10,000 Kip which consists of 190 reponsdents accounted for 59.7 % and the least willing to pay for the fee is 33,750 Kip which consists of 7 respondents accounting for 2.2%. In terms of international tourists, the most willing to pay is 16,000 Kip, consisting of 39 respondents and equaled 47.6%. The least willing to pay is 81,000 Kip, consists of 2 repondents and cover 2.4%. In the analysis of variables of socio-economic and WTP show that the local visitors, it discovers that ages, marital status and occupation has relationship with WTP with stastistic significant level at 0.01. The gender of the repondents has relationship with WTP in the significant at 0.05. For the imcome and return to visit the site next time no relationship with WTP. The foreign respondents, it finds out that gender, monthly imcome and visitors return to visit jar site have relationship with WTP in significant at 0.01. The age and education have the relationship with WTP with significance level 0.05, while the marital status and occupation have no relationship with WTP. In terms of economic evaluation of the Plain of Jar 1st, the outcome of both domestic and foreign visitor’s figure is 7,024,788,720 Kip per year.